Identification of critical success factors for enhancing virtual project team performance in South Africa's local government context - Lande, Kwanda (Department of Construction Economics and Management, 2025)
Internationally, virtual project teams have surfaced as an essential organizational structure due to improved information and communication technology and changes in corporate values. Furthermore, virtual project teams are favoured for the flexibility they provide in terms of recruiting the best available experts regardless of their location, improving productivity by reducing commuting time and operational costs for organizations. Despite this, virtual project teams are also associated with many challenges, linked to communication, collaboration and sharing of information, that negatively affect Virtual Project Team Performance (VPTP). Hence, identifying what enhances VPTP is of great importance. This research aimed to identify Critical Success Factors (CSFs) for enhancing VPTP in the South African local government context (focusing on the City of Cape Town), determine the interrelationship between the identified CSFs, and identify CSFs to prioritize when implementing and managing virtual project teams. The research participants for this study identified 20 CSFs using Interactive Management methodology techniques linked to CSF generation, and CSF clarification processes. Moreover, research participants generated an Interpretive Structural Model (ISM) that illustrates the CSFs that "significantly help to achieve” other CSFs. Using the transitive logic inferences embedded in the ISM program, this research has revealed that CSFs such as shared values among team members, regular team brainstorming sessions, reviewing lessons learned of previous projects, effective communication, technical skills competencies aligned to tasks, project progress and performance management, time management and boundaries, reliable technology and network system, and regular in-person engagements even when virtual working is the norm, are relatively important based on the number of other CSFs that they significantly help to achieve. The benefit of this study is twofold: firstly, it helps to extend prior research on CSFs for VPTP by contributing new information based on the views and experiences of virtual project team stakeholders in the South African local government context. Secondly, this research is essential for South African municipalities as it identifies CSFs in one municipality that other municipalities can use as a base to build from in identifying and implementing CSFs for VPTP in their organizations.